Interface Engineering for Lithium Metal Anodes in Liquid Electrolyte. Issue 34 (30th July 2020) - Zhai, Pengbo; Liu, Lixuan; Gu, Xiaokang; Wang, Tianshuai; Gong, Yongji
Abstract: Interfacial chemistry between lithium metal anodes and electrolytes plays a vital role in regulating the Li plating/stripping behavior and improving the cycling performance of Li metal batteries. Constructing a stable solid electrolyte interphase (SEI) on Li metal anodes is now understood to be a requirement for progress in achieving feasible Li‐metal batteries. Recently, the application of novel analytical tools has led to a clearer understanding of composition and the fine structure of the SEI. This further promoted the development of interface engineering for stable Li metal anodes. In this review, the SEI formation mechanism, conceptual models, and the nature of the SEI are briefly summarized. Recent progress in probing the atomic structure of the SEI and elucidating the fundamental effect of interfacial stability on battery performance are emphasized. Multiple factors including current density, mechanical strength, operating temperature, and structure/composition homogeneity that affect the interfacial properties are comprehensively discussed. Moreover, strategies for designing stable Li‐metal/electrolyte interfaces are also reviewed. Finally, new insights and future directions associated with Li‐metal anode interfaces are proposed to inspire more revolutionary solutions toward commercialization of Li metal batteries. Abstract : The interfacial chemistry between Lithium metal anodes and electrolytes is vital in regulating Li plating/stripping behavior and improving the cycling performance of Li metal batteries. Key achievements in formation mechanisms, conceptual models, and structural characteristics of solid electrolyte interphases utilizing advanced analytical tools are summarized. Factors affecting interfacial stability and corresponding strategies for stabilizing anode/electrolyte interface are also presented.